WHO EDUCATES MATHEMATICALLY GIFTED STUDENTS: PERSPECTIVES OF PROSPECTIVE MATHEMATICS TEACHERS - Gönül Yazgan-Sağ (Istraživanja u Pedagogiji, 2025)
This qualitative research aimed to examine prospective mathematics teachers’ perspectives about the teachers of mathematically gifted students. The participants of this study were 17 prospective secondary mathematics teachers and 23 prospective primary mathematics teachers, 40 prospective mathematics teachers in total, who have received their education at a state university in Turkey. In order to collect the data, (i) written explanations of all prospective mathematics teachers, (ii) one whole-class discussion with primary mathematics teachers, and (iii) three focus group interviews with both primary and secondary mathematics teachers were used. Content analysis was used while analyzing the data. The findings indicated that prospective mathematics teachers mostly associated teachers of mathematically gifted students with teachers’ personality traits. They also took into account teachers’ content knowledge and pedagogical knowledge. They highlighted the importance of mathematical content knowledge while educating mathematically gifted students. The prospective mathematics teachers also emphasized having knowledge of giftedness and gifted education.